Rethinking the Relationship between Insulin and Cancer. (August 2020) - Vigneri, R.; Sciacca, L.; Vigneri, P.
Abstract : In addition to being a major metabolic hormone, insulin is also a growth factor with a mitogenic effect on all cells, more marked in malignant cells that often overexpress the insulin receptor. In patients with metabolic diseases characterized by hyperinsulinemia (obesity, type 2 diabetes, and metabolic syndrome), the incidence of several types of cancer is increased, as is cancer-related mortality. Because of the worldwide growing prevalence of metabolic diseases and the diffuse use of insulin and its analogs for treating diabetes, the relationship between insulin and cancer has become a clinically relevant issue. Clinical studies have not clarified the degree to which hyperinsulinemia can influence cancer occurrence and prognosis. To better understand this issue, an improved scientific approach is required, with more careful consideration of the mechanisms related to hyperinsulinemia and carcinogenesis. Highlights: Metabolic diseases (obesity and type 2 diabetes) that are characterized by hyperinsulinemia are associated with both increased cancer risk and increased cancer-related mortality. Since insulin is also a growth factor and effectively stimulates cancer cell growth in vitro, insulin excess is assumed to be a cancer-promoting factor in patients. Our understanding of the insulin–cancer relationship is incomplete, and clinical studies have not clarified its relevance because of inappropriate design, assuming hyperinsulinemia as a univocal condition and assembling together heterogeneous cancers with unknown insulin sensitivity. We need to better understand the degree to which hyperinsulinemia influences cancer prognosis above and beyond the intrinsic cancer characteristics determined by malignant cells' biological profile. We also need to identify whether all cancers or only some of them are insulin-sensitive and how to recognize them in patients.